2006
DOI: 10.1007/bf03022833
|View full text |Cite
|
Sign up to set email alerts
|

L’administration péridurale de dexaméthasone réduit la douleur et la demande d’analgésiques postopératoires

Abstract: Purpose: Epidural steroids may have potential advantages for providing postoperative analgesia. We therefore undertook a study to evaluate the efficacy of epidurally administered dexamethasone in reducing postoperative morphine requirements, as a measure of analgesia following laparoscopic cholecystectomy. Methods:In a randomized, double-blind study, 94 patients undergoing laparoscopic cholecystectomy were randomly assigned to one of three groups. Group 1 (Control) patients received dexamethasone 5 mg iv with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
75
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 29 publications
(38 reference statements)
4
75
1
1
Order By: Relevance
“…Previous studies in humans showed that lower doses of epidural dexamethasone may be effective in surgical procedures associated with mild or moderate pain such as laparoscopy, orchiopexy and herniorrhaphy 1,10 .…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in humans showed that lower doses of epidural dexamethasone may be effective in surgical procedures associated with mild or moderate pain such as laparoscopy, orchiopexy and herniorrhaphy 1,10 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…Inadequate postoperative pain relief can delay recovery and increase the incidence of adverse effects, such as delayed healing, lack of appetite and decreased immunity 1 . Female dogs undergoing ovariohysterectomy (OVH) suffer pain of varying severity (mild-tomoderate) depending on the degree of surgical trauma, requiring analgesic drugs in the first postoperative day 2 .…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute noxious stimulation of peripheral tissues leads to sensitization of dorsal horn neurons of the spinal cord by the release of excitatory amino acids such as glutamate and aspartate. These amino acids activate N-methyl-Daspartate receptors resulting in calcium ion influx (24). The increased intracellular calcium leads to activation of phospholipase A2, the rate-limiting enzyme in prostaglandin synthesis, which converts membrane phospholipids to arachidonic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Since patients complained about back pain after surgical interventions-mostly related to bad positioning or pre-existing discogenic disease-on the supposition that postoperative pain should be treated preventively, patients received 1 mg morphine with 80 mg of methylprednisolone epidurally directly after surgery (Joos et al, 1993). Preoperative epidural administration of dexamethasone 5 mg, with or without bupivacaine, reduced postoperative pain and morphine consumption following laparoscopic cholecistectomy (Thomas et al, 2006). Studies about epidural methylprednisolone-morphine compositions in orthopaedic knee surgery showed comparable or even superior analgesic effect with bupivacaine-morphine mixture .…”
Section: Introductionmentioning
confidence: 99%